2008
DOI: 10.1373/clinchem.2007.099747
|View full text |Cite
|
Sign up to set email alerts
|

Plasma PCSK9 Concentrations Correlate with LDL and Total Cholesterol in Diabetic Patients and Are Decreased by Fenofibrate Treatment

Abstract: BACKGROUND:Proprotein convertase subtilisin/kexin type 9 (PCSK9) promotes the degradation of the LDL receptor (LDLr) in hepatocytes, and its expression in mouse liver has been shown to decrease with fenofibrate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
94
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(121 citation statements)
references
References 30 publications
(38 reference statements)
24
94
0
1
Order By: Relevance
“…demonstrated that PPAR-α activation resulted in the repression of PCSK9 promoter activity, and in the up-regulation of PC5/6A and furin, which degrade PCSK9 [9]. To our knowledge, two clinical studies suggest that fenofibrate treatment was associated with decrease in PCSK9 levels [24,25]. Lambert et al [24] reported that fenofibrate 200 mg/day was associated with decrease (-8.5%; p = 0.041) in PCSK9 level in diabetic patients and Chan et al [25] showed fenofibrate 145 mg/day was associated with decrease (-13%; p < 0.05) in statin treated T2DM subjects.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…demonstrated that PPAR-α activation resulted in the repression of PCSK9 promoter activity, and in the up-regulation of PC5/6A and furin, which degrade PCSK9 [9]. To our knowledge, two clinical studies suggest that fenofibrate treatment was associated with decrease in PCSK9 levels [24,25]. Lambert et al [24] reported that fenofibrate 200 mg/day was associated with decrease (-8.5%; p = 0.041) in PCSK9 level in diabetic patients and Chan et al [25] showed fenofibrate 145 mg/day was associated with decrease (-13%; p < 0.05) in statin treated T2DM subjects.…”
Section: Discussionmentioning
confidence: 85%
“…To our knowledge, two clinical studies suggest that fenofibrate treatment was associated with decrease in PCSK9 levels [24,25]. Lambert et al [24] reported that fenofibrate 200 mg/day was associated with decrease (-8.5%; p = 0.041) in PCSK9 level in diabetic patients and Chan et al [25] showed fenofibrate 145 mg/day was associated with decrease (-13%; p < 0.05) in statin treated T2DM subjects. In contrast to these reports, Mayne et al and Troutt et al represented an increase in circulating PCSK9 level after fenofibrate treatment with 200 mg/day in dyslipidemic patients (+17%; p = 0.031 and +25%; p < 0.01, respectively) [8,10], although the precise mechanism contributing to these increases remains to be clarified.…”
Section: Discussionmentioning
confidence: 97%
“…Their effects on PCSK9 mRNA levels have been explored with mixed results. They have been shown to repress PCSK9 gene expression in a human hepatocyte cell line and isolated mouse hepatocytes, 85,86 but the WY14643 agonist had no effect on the level of PCSK9 mRNA in isolated hamster hepatocytes. 87 The reasons for this discrepancy are unclear as are those from clinical studies in fibrate-treated patients, showing increased plasma PCSK9 levels in most studies [88][89][90][91] and a decreased levels in another.…”
Section: Nuclear Receptorsmentioning
confidence: 97%
“…87 The reasons for this discrepancy are unclear as are those from clinical studies in fibrate-treated patients, showing increased plasma PCSK9 levels in most studies [88][89][90][91] and a decreased levels in another. 85 PPARγ ligands, 15d-PGJ1 or pioglitazone, have been shown to augment the level of PCSK9 mRNA in HepG2 cells. This induction can also be achieved by preventing phosphorylation of the receptor by extracellular-regulated kinases 1 and 2 with such specific inhibitors PD98059 or U0126.…”
Section: Nuclear Receptorsmentioning
confidence: 99%
“…Serum PCSK9 measured by ELISA seems directly correlated with serum LDL-C and total cholesterol [Alborn et al, 2007]. Atorvastatin (40 mg/ day) increases human serum levels of PCSK9 by 34% compared with baseline and placebo [Careskey et al, 2008], while fenofibrate (200 mg/day) decreased plasma PCSK9 concentrations by 8.5% in diabetic patients [Lambert et al, 2008]. However, a standardized method, with specific antibodies, is still needed to compare the levels of PCSK9 measured in different studies.…”
Section: Diagnostic Relevancementioning
confidence: 99%